Novel insights into the phylogeographic patterns of ascidians fouling Greek mussel cultures - Georgios Geladakis; Charikleia Papaioannou; Vasiliki Kommata; Athanasios Lattos; Dimitrios K. Papadopoulos; Ioannis A. Giantsis; John A. Theodorou; Costas Batargias (Marine Biodiversity, 2025)

Status, distribution, and threats of the last surviving fan mussel populations in Greece - ORESTIS PAPADAKIS; IOANNIS MAMOUTOS; ALEXIS RAMFOS; GAETANO CATANESE; EVANGELOS PAPADIMITRIOU; JOHN THEODOROU A.; COSTAS BATARGIAS; CHARIKLEIA PAPAIOANNOU; MARIA KAMILARI; ELINA TRAGOU; VASSILIS ZERVAKIS; STELIOS KATSANEVAKIS (Mediterranean Marine Science, 2023)
Since the first confirmed records of mass mortality events (MME) in the Aegean Sea in 2018, Pinna nobilis populations in Greek seas have been decimated. To bolster recovery efforts, this study aimed to assess the status of fan mussel populations in the Aegean and Ionian seas and investigate potential recolonization through natural recruitment. From May 2022 to May 2023, 163 independent underwater visual surveys were conducted across various locations and depths along the Greek coastline. A total of 4348 P. nobilis individuals was recorded, of which 87.3% were found dead and 12.7% were alive. The sole surviving fan mussel populations were located in the semi-enclosed gulfs of Amvrakikos in the Ionian Sea and of Kalloni in the Aegean Sea, with estimated recent mortality rates (excluding potential poaching) of 7.7% and 6.3%, respectively. To track potential new recruitment, a network of larvae collectors was deployed in multiple locations. Additionally, an ocean circulation model (OCM) was developed to predict the export and fate of larvae from the surviving populations in the Marmara Sea towards the Aegean Sea. Beyond the MME, this study identified several other threats, which significantly endanger fan mussel survival. The findings of this study underscore the urgent need to implement protection measures and restoration actions to enhance the chances of P. nobilis survival and recovery in the Greek seas.

High Resolution Melting (HRM) Genotyping in the Genus Origanum: Molecular Identification and Discrimination for Authentication Purposes - Charikleia Papaioannou; Konstantina Zeliou; Panayiotis Trigas; Vasileios Papasotiropoulos (Biochemical Genetics, 2020)